CAN DIFFERENCES MAKE A DIFFERENCE? A COMMENT ON TILLICH'S PROPOSALS FOR DIALOGUE BETWEEN RELIGIONS - Bowker, John W. (The journal of theological studies, 1973)
JOHN W. BOWKER; CAN DIFFERENCES MAKE A DIFFERENCE? A COMMENT ON TILLICH'S PROPOSALS FOR DIALOGUE BETWEEN RELIGIONS, The Journal of Theological Studies, Volume X